(untitled) (Scientific journal of the Fergana State University, 2024)
This article presents a scientific analysis of the spiritual and educational significance of kapsha kupasha in the context of globalization. The article also scientifically highlights that in the fight against missionary work, spirituality as a powerful force has the miraculous power of betakpop, personifying conflict spirituality as a powerful force, it is a mouthpiece for the great and glorious goal of our nation, our people.